Categories in Text and Talk / A Practical Introduction to Categorization Analysis - Lepper Georgia (Sage Publications, 2000)
The first practical book on how to apply Harvey Sacks' membership categorization analysis technique which is an increasingly important and influential method within the field of conversation analysis. Preface, Introducing Categorization Analysis, Practicing the Art of Categorization Analysis, First Principles, Practicing the Art of Categorization Analysis: Further Developments, Analyzing Culture Using Talk and Text and Image, Analyzing Context, Analyzing Talk, Analyzing Text, Analyzing Images, Analyzing Narrative, What is a Narrative?, Applying Categorization Analysis to the Study of Naturally Occurring Stories, Contemporary Application of Sacks' Work on Narrative, Analyzing Organizations, Background to the Study of Organizations, The Contribution of CA, A Case Study, The Practice of Research, Reliability and Validity, Working with an Extended Textual or Conversational Data: The Uses and Abuses of Computer-Aided Analysis, Ethics in Research, Glossary, References, Name and Subject Index.